Optimal Contract to Induce Continued Effort - Sun, Peng; Tian, Feng (Management Science, 2018)
We consider a basic model of a risk-neutral principal incentivizing a risk-neutral agent to exert effort to raise the arrival rate of a Poisson process. The effort is costly to the agent, is unobservable to the principal, and affects the instantaneous arrival rate. Each arrival yields a constant revenue to the principal. The principal, therefore, devises a mechanism involving payments and a potential stopping time to motivate the agent to always exert effort. We formulate this problem as a stochastic optimal control model with an incentive constraint in continuous time over an infinite horizon. Although we allow payments to take general forms contingent on past arrival times, the optimal contract has a simple and intuitive structure, which depends on whether the agent is as patient as or less patient than the principal toward future income. This paper was accepted by Manel Baucells, decision analysis.